Role of serum neuron-specific enolase levels in the early diagnosis and prognosis of sepsis-associated encephalopathy: a systematic review and meta-analysis - Pei, MengQin; Yang, YuShen; Zhang, ChunYan; Huang, QiaoMei; Fang, YuMing; Xu, LiMing; Lin, Shu; He, HeFan (Frontiers in Neurology, 2024)
To investigate the early diagnostic and prognostic value of serum neuron-specific enolase (NSE) in sepsis-associated encephalopathy (SAE), a systematic review and meta-analysis of clinical trials in PubMed, Web of Science, Embase, and Cochrane was performed. This study was registered in PROSPERO as CRD42023433111. Eleven studies involving 1259 serum samples from 947 patients with sepsis were included in the analysis. The serum NSE levels of patients with SAE were higher than those of the non-encephalopathy sepsis group (mean deviation, MD,.50, Z=5.9, P < 0.00001]), and the serum NSE levels of deceased patients with sepsis were higher than those of survivors (MD, Z=5.41, P < 0.00001]). Elevated serum NSE levels in patients with sepsis are associated with early SAE diagnosis and mortality; therefore, serum NSE may be a valid biomarker for early SAE diagnosis and prognosis.